Los medios de comunicación tecnológicos y su influencia en la conducta de los estudiantes del nivel de Educación Inicial 2 de la Unidad Educativa FAE N° 5 en el período 2020-2021. - Neto Chusín, Sandra Lorena (2020)
The use of the technological media are a fundamental part of daily life, however, the problem is in how they are used, the lack of control and the content to which, especially younger children, have access. Human behavior can be affected by various factors, between these the influence of the technological media, which, although it is true, has a positive impact, it also does so negatively. The present research work: "The technological communication media and its influence in children´s behavior” was carried out in the FAE Educational Unit No. 5 at Initial Education Level 2, in a population of 75 children aged 4 years; the fundamental objective of this research was to determine the influence of technological communication media on the behavior of students. The methodology used in this study has a quantitative approach with the deductive method, that is, it is based on the existing theories to support the two variables, in this way, through the diagnosis, the theories could be verified with the reality of the educational community where they were applied the proposal. The results obtained were favorable since by means of the work carried out jointly with parents, they helped to promote the use of applications and programs with educational content, habits, schedules and norms of appropriate use were established in this way, it was possible to improve the behavior and avoid the appearance of disruptive and inappropriate behaviors in student